Evidence for the Involvement of Lamins in Aging - Rodriguez, Sofia; Eriksson, Maria (Current Aging Science, 2010)
The molecular mechanisms that cause physiological aging are still not completely understood, most likely because of the complex nature of the aging process. Recent discoveries on segmental progeroid syndromes emphasize the importance of studying rare diseases to discover more common mechanisms. Since the identification of mutations in the LMNA gene that causes the segmental progeroid syndrome, Hutchinson-Gilford progeria syndrome (HGPS), there has been an increasing interest in the potential role for lamins in the normal aging process. Recent data provide support for the shared mechanisms between natural and pathological aging, and show that further studies of HGPS and segmental progeroid syndromes will be of use in solving the aging puzzle. In this review, we summarize the recent findings and discuss the existing evidence for an important functional link between lamins and the aging process. In addition, we discuss the evidence for a mechanism in which defects in lamins result in genomic instability and senescence.
Keywords: Hutchinson-Gilford progeria syndrome